Respostas
respondido por:
2
x = 5y
7x - 20y = 45 ( 7x = 20y +45 )
Substituindo na primeira equação:
x = 5y
20y + 45 = 5y
15y = -45
y = -3
Substituindo o resultado de Y na segunda equação:
7x - 20y = 45
7x - 20.(-3) = 45
7x +60 = 45
7x = -15
x = -15 / 7
7x - 20y = 45 ( 7x = 20y +45 )
Substituindo na primeira equação:
x = 5y
20y + 45 = 5y
15y = -45
y = -3
Substituindo o resultado de Y na segunda equação:
7x - 20y = 45
7x - 20.(-3) = 45
7x +60 = 45
7x = -15
x = -15 / 7
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás